2017
DOI: 10.1007/s11255-017-1545-7
|View full text |Cite
|
Sign up to set email alerts
|

High expression of ASPM correlates with tumor progression and predicts poor outcome in patients with prostate cancer

Abstract: Our data suggest that ASPM may play an important role in the progression of PCa. More importantly, the increased expression of ASPM may potentially predict poor BCR-free survival in patients with PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 24 publications
4
38
0
Order By: Relevance
“…e purpose of this study was to assess the critical role that ASPM plays in the development of cancer and determine whether it can be used as a biomarker for bladder cancer. Recent literature reports that ASPM expression disorders are associated with the progression of epithelial ovarian cancer [36], colorectal cancer [37], prostate cancer [38], and hepatocellular carcinoma [39]. Consistent with our research, increased expression of ASPM in bladder cancer patients is associated with poor prognosis [40].…”
Section: Discussionsupporting
confidence: 91%
“…e purpose of this study was to assess the critical role that ASPM plays in the development of cancer and determine whether it can be used as a biomarker for bladder cancer. Recent literature reports that ASPM expression disorders are associated with the progression of epithelial ovarian cancer [36], colorectal cancer [37], prostate cancer [38], and hepatocellular carcinoma [39]. Consistent with our research, increased expression of ASPM in bladder cancer patients is associated with poor prognosis [40].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have prevailingly focused on the relationship between ASPM gene mutations and autosomal recessive primary microcephaly and abnormal neuronal differentiation [44] . Nevertheless, except for its role in normal physiological regulatory functions, recent studies have also found that the upregulation of ASPM promotes the metastasis of tumors, including prostate cancer, endometrial cancer, melanomas, bladder cancer, clear cell renal cell carcinoma [45][46][47][48][49] . Pai et al [50] previously pointed out that overexpression of ASPM has energetically in uence on prostate cancer cell proliferation and invasion, as it could enhance the Wnt-induced βcatenin transcriptional activity through interacting with disheveled-3, which is a cardinal upstream regulator of Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…ASPM is known for its role in spindle microtubule organization in cell division (53). The high expression of ASPM was also observed in several other cancers such as bladder cancer (54), hepatocellular carcinoma (55), gliomas (56), ovarian cancer (57) and prostrate cancer (58) where the increase in expression was mostly associated with tumour grade, early recurrence, tumour metastasis and worse survival. Moreover, knockdown of ASPM in pancreatic cancer cell lines reduced cell proliferation and migration (59).…”
Section: Discussionmentioning
confidence: 96%
“…This analysis identi ed 4709 CNV segments in IDCs when compared to NAT, with 65% associated with gains and 35% with losses (Table S1). Similarly, in LNmets, a total of 1725 CNV segments were identi ed with 58.9% associated with gains and 41.1% losses (Table S2), which were not present in NATs. All CNV segments ranged from more than one kilobase to several megabases in size.…”
Section: Cnvs In Idcs and Lnmets Compared To Nat Samplesmentioning
confidence: 99%